Arahan Pengembangan Desa Wisata di Desa Pincara Kabupaten Luwu Utara - Budiarti, Wiwik; Siradjuddin, Irsyadi; Idham AP., Andi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
The Pincara Village area has one of the potential of a tourist village in Masamba District, North Luwu Regency. Pincara Tourism Village has a beautiful landscape so that it can be used as a natural tourism object with the uniqueness, authenticity, social, and culture of the community. The development of the potential of the Pincara Tourism Village must be more focused so that its development and development can be better. The aim of the research is to see the feasibility of the Pincara Tourism Village and to find out the direction for the development of the Tourism Village. In achieving the objectives of the research, several stages of tourism potential analysis were carried out in order to determine the potential attractiveness of the Pincara tourism village which was feasible to be developed, besides using a SWOT analysis in determining the development directions that must be carried out in determining the development direction that will be applied to the Tourism Village. The result of this research is that Pincara Tourism Village is a tourism village that is feasible to be developed with excellent village potential to further improve the development strategy carried out in the form of a Master Plan for the development of the Tourism Village area, maximizing the processing of tourism potential, increasing government cooperation with the community in developing village potential, utilizing the functional relationship of the surrounding villages.